Comparison of Oxidative Stress and Inflammation Induced by Different Intravenous Iron Sucrose Similar Preparations in a Rat Model - Toblli, Jorge Eduardo (2012)
Iron sucrose originator (IS(ORIG)) has been used to treat iron deficiency and iron deficiency anemia for decades. Iron sucrose similars (ISSs) have recently entered the market. In this non-clinical study of non-anemic rats, five doses (40 mg iron/kg body weight) of six ISSs marketed in Asian countries, IS(ORIG) or saline solution (control) were administered intravenously over four weeks to compare their toxicologic effects. Vasodilatory effects, impaired renal function and hepatic damage were only observed in the ISS groups. Significantly elevated serum iron and transferrin saturation levels were observed in the ISS groups suggesting a higher release of iron resulting in higher amounts of non-transferrin bound (free) iron compared to IS(ORIG). This might explain the elevated oxidative stress and increased levels of inflammatory markers and antioxidant enzymes in the liver, heart and kidneys of ISS-treated animals. Physico-chemical analyses showed that the molecular structure of most of the ISSs differed greatly from that of the IS(ORIG). These differences may be responsible for the organ damage and oxidative stress observed in the ISS groups. Significant differences were also found between different lots of a single ISS product. In contrast, polarographic analyses of three different IS(ORIG) lots were identical, indicating that the molecular structure and thus the manufacturing process for IS(ORIG) is highly consistent. Data from this study suggest that ISSs and IS(ORIG) differ significantly. Therefore, before widespread use of these products it would be prudent to evaluate additional non-clinical and/or clinical data proving the safety, therapeutic equivalence and interchangeability of ISSs with IS(ORIG).